Safranal Attenuates Malathion-Induced Oxidative Stress and AChE Inhibition Across Blood, Hepatic, Renal, and Brain Matrices - Ahmet Büyükben; Ömer Hazman; Laçine Aksoy; Funda Karabağ (Animal Health Production and Hygiene, 2026)
Organophosphate pesticides, particularly malathion, are widely used in agriculture but pose severe toxicity risks to non-target organisms through acetylcholinesterase (AChE) enzyme inhibition and the induction of oxidative stress. This study investigated the potential protective effects of safranal, a primary bioactive component of saffron (Crocus sativus L.) known for its antioxidant and anti-inflammatory properties, against malathion-induced systemic and tissue-specific toxicity. Experimental groups were evaluated by measuring malondialdehyde (MDA), nitric oxide (NO), glutathione (GSH), superoxide dismutase (SOD), catalase (CAT), and GPx (glutathione peroxidase) levels, alongside AChE enzyme activity in the blood, liver, kidney, and brain tissues. The findings demonstrated that malathion exposure caused profound toxicity characterized by severe AChE inhibition, accelerated lipid peroxidation, elevated NO levels, and a critical depletion of both enzymatic and non-enzymatic antioxidant defenses across all analyzed matrices. Conversely, safranal administration served as an effective therapeutic intervention. It mitigated oxidative damage, limited the exhaustion of key antioxidant enzymes by reducing reactive oxygen species, and supported the preservation of AChE functionality. Notably, safranal’s protective efficacy exhibited tissue-dependent variations; while it significantly attenuated oxidative stress markers and preserved cellular viability in the plasma, liver, and renal matrices, it demonstrated limited protective capacity in brain tissue under the current experimental conditions. In conclusion, safranal represents a promising bioactive countermeasure against organophosphate-induced systemic injury. However, further research is warranted to elucidate its precise transport mechanisms and potential limitations in crossing the blood-brain barrier.